Statin induced myopathy: a case report - M. S., Brunda; Dharmaplaiah, Chethana; Doraisamy, Prakash; S., Maheswaran (International Journal of Research in Medical Sciences, 2023)
Statin-induced necrotizing autoimmune myopathy is an immune-mediated necrotizing myopathy related to the use of statins. It is a very rare disease, which usually presents with proximal muscle weakness and frank elevation in creatine kinase levels. Stopping statin and the use of immunosuppressive therapy are considered the mainstay therapy. Herein, we present a case of a 75-year-old patient with statin-induced myopathy based on the presence of proximal muscle weakness, magnetic resonance findings. The patient was treated with IVIg and corticosteroid therapy with a particularly good response to intravenous immunoglobulin. However, medications are accompanied by the not so friendly adverse events. Through this report we highlight the importance of understanding. This report highlights the importance of timely diagnosis and early use of combined immunosuppressive therapy to improve patients’ outcome affected by this rare disease.